The relationship between dental caries, dietary intake and body composition in school-age children - İrem Çağla Özel; Gizem Erbaş Ünverdi; Pınar Serdar Eymirli; Nurcan Yabancı Ayhan (Egyptian Pediatric Association Gazette, 2024)
Abstract Objective The aim of this study is to evaluate the relationship between dental caries, food intake, and body composition in school-age children. Methods The study was conducted on 210 children, 105 boys and 105 girls, aged 6–12 years, without mental and/or physical disorders. Oral examinations of the children were performed by paediatric dentists and DMFT–DMFS and dmft–dmfs values were recorded. A detailed food frequency questionnaire was applied to determine the consumption frequency of dairy products and sugar‐added foods. Children’s height, waist and hip circumference measurements were taken by the researcher; body weight and body composition were evaluated with a Tanita body analyzer. Results The DMFS value of children who consumed white cheese daily is lower than children who did not (p < 0.05). The DMFT and DMFS values were found to be higher in children who consumed sweets, biscuits, and spreadable chocolate daily compared to children who did not (p < 0.05). Body weight and waist circumference are positively correlated with DMFT and negatively correlated with dmft. BMI is positively correlated with DMFT and negatively correlated with dmft (p < 0.05). In binary logistic regression, it was found that maternal education level, frequency of added sugar intake and body fat ratio were predictors of the presence of caries. Conclusion In this study, dental caries was associated with food consumption and body mass index. In children, consumption of sugary foods should be reduced and consumption of dairy products should be increased.